The dose–effect relationship between acupuncture and its effect on primary insomnia: a systematic review and meta-analysis - Zhang, Xiaoni; Wang, Yue; Liu, Chengyong; Qin, Shan; Lin, Liyu; Dong, Can; Wu, Wenzhong; Chen, Zhaoming (Frontiers in Psychiatry, 2025)
BackgroundThe benefits of acupuncture on primary insomnia (PI) have been well established in previous studies. However, different acupuncture dosages may lead to controversy over its efficacy. Therefore, this systematic review and meta-analysis was conducted to assess the relationship between the dose and efficacy of acupuncture for the treatment of PI.MethodsSeven databases were searched from inception until May 30, 2024. The included randomized controlled trials (RCTs) with acupuncture for PI on the Pittsburgh Sleep Quality Index (PSQI) scores were divided into three categories according to the therapeutic dose of acupuncture (frequency, session, and course): low dosage, medium dosage, and high dosage. The correlation between the dose and the effect of treatment was analyzed. Risk of bias was assessed using Cochrane Collaboration’s risk of bias tool. Meta-analyses were performed using RevMan v.5.4 and Stata 16.0 software.ResultsA total of 56 studies were included. There were 17 sham acupuncture-controlled RCTs that are notable because of their high quality. Overall, the effect on the reduction of the PSQI scores varied across the different acupuncture dosages. For the frequency of acupuncture, the results showed a significant improvement in the moderate frequency (three sessions per week) and high frequency (five to seven sessions per week) categories. With regard to the acupuncture session, it was shown that moderate session (12–20 sessions) and high session (24–30 sessions) had better effects on the reduction of the PSQI scores, with low session (≤10 sessions) being not significant. For the acupuncture course, there were no differences in the short course (≤2 weeks) and the long course (>4 weeks) between the acupuncture group and the control group. Medium course (3–4 weeks) was considered as the optimal course. In addition, there were no differences between acupuncture and SATV (sham acupuncture therapy at verum points) on the same acupuncture points in the PSQI scores. The results of GRADE assessment demonstrated that the level of evidence was very low to moderate, probably due to the poor methodological quality and the substantial heterogeneity among studies.ConclusionsA dose–effect relationship was found between the acupuncture dose and the PSQI scores. Although sham acupuncture needling at the same points as those in acupuncture may not be a true placebo control, this was utilized in a minority of studies. Collectively, the data suggest that at least three sessions per week for 3–4 weeks and a total of at least 12 acupuncture sessions would be the optimal clinical response.Systematic review registrationhttps://www.crd.york.ac.uk/, identifier CRD42024560078.